Molecular pathology of prostate cancer. Issue 7 (23rd June 2005) - Hughes, C; Murphy, A; Martin, C; Sheils, O; O'Leary, J
Abstract : The molecular pathology of prostate cancer is complex; not only are multiple genes involved in its pathogenesis, but additional environmental factors such as diet and inflammation are also involved. The exhaustive research into prostate cancer to date has demonstrated a complex interaction of multiple genes and environmental factors, some of which may be more important in individual prostate cancer cases. This is an exciting era, with the emergence of new investigative tools such as DNA microarray technology and the application of the field of proteomics to the study of human cancers. Knowledge of genetic changes underlying the initiation, development, and progression of prostate cancer is accumulating rapidly. With increasing knowledge, it may be possible to distinguish indolent from aggressive prostate tumours by molecular fingerprinting. This review discusses the most consistently reported molecular pathological findings in hereditary and sporadic prostate cancer, together with new concepts and technologies.